Metabolic engineering of Pichia pastoris for production of isobutanol and isobutyl acetate - Wiparat Siripong; Philipp Wolf; Theodora Puspowangi Kusumoputri; Joe James Downes; Kanokarn Kocharin; Sutipa Tanapongpipat; Weerawat Runguphan (Biotechnology for Biofuels, 2018)
Abstract Background Interests in renewable fuels have exploded in recent years as the serious effects of global climate change become apparent. Microbial production of high-energy fuels by economically efficient bioprocesses has emerged as an attractive alternative to the traditional production of transportation fuels. Here, we engineered Pichia pastoris, an industrial workhorse in heterologous enzyme production, to produce the biofuel isobutanol from two renewable carbon sources, glucose and glycerol. Our strategy exploited the yeast’s amino acid biosynthetic pathway and diverted the amino acid intermediates to the 2-keto acid degradation pathway for higher alcohol production. To further demonstrate the versatility of our yeast platform, we incorporated a broad-substrate-range alcohol-O-acyltransferase to generate a variety of volatile esters, including isobutyl acetate ester and isopentyl acetate ester. Results The engineered strain overexpressing the keto-acid degradation pathway was able to produce 284 mg/L of isobutanol when supplemented with 2-ketoisovalerate. To improve the production of isobutanol and eliminate the need to supplement the production media with the expensive 2-ketoisovalerate intermediate, we overexpressed a portion of the amino acid l-valine biosynthetic pathway in the engineered strain. While heterologous expression of the pathway genes from the yeast Saccharomyces cerevisiae did not lead to improvement in isobutanol production in the engineered P. pastoris, overexpression of the endogenous l-valine biosynthetic pathway genes led to a strain that is able to produce 0.89 g/L of isobutanol. Fine-tuning the expression of bottleneck enzymes by employing an episomal plasmid-based expression system further improved the production titer of isobutanol to 2.22 g/L, a 43-fold improvement from the levels observed in the original strain. Finally, heterologous expression of a broad-substrate-range alcohol-O-acyltransferase led to the production of isobutyl acetate ester and isopentyl acetate ester at 51 and 24 mg/L, respectively. Conclusions In this study, we engineered high-level production of the biofuel isobutanol and the corresponding acetate ester by P. pastoris from readily available carbon sources. We envision that our work will provide an economic route to this important class of compounds and establish P. pastoris as a versatile production platform for fuels and chemicals.